Penanganan Perkara Penggunaan Senjata Tajam oleh Terdakwa yang Diduga Mengalami Gangguan Jiwa (Analisis Putusan Nomor 160/Pid.Sus/2022/PN Sbs) - Nisrina Meidi Latifa; Cahyo Cahyo (PT Elaborium Elevasi Indonesia, 2026)
This study examines the investigation of perpetrators of sharp weapon abuse suspected of having mental disorders, focusing on the role of psychiatric testimony in influencing the judge’s decision in the Sumbawa Besar District Court Decision No. 160/Pid.Sus/2022/PN Sbs. While the abuse of sharp weapons fulfills the criminal elements under Emergency Law No. 12 of 1951, the criminal sanction depends on the defendant's ability to be held responsible, as stated in Article 44 of the Criminal Code and the principle of geen straf zonder schuld (no punishment without guilt). This study uses a normative juridical method with a legislative and case law approach, analyzed descriptively and analytically. The results show that during the investigation, the perpetrator’s psychiatric condition was not considered, and psychiatric examination only became significant during the trial stage. The psychiatrist’s testimony played a crucial role in evaluating the defendant’s responsibility and the application of Article 44 of the Criminal Code by the judge. This study highlights the importance of conducting psychiatric examinations carefully from the investigation stage to ensure substantive justice, the effectiveness of the criminal justice process, and the protection of human rights.